Swift River - Chambers, Essie (Simon & Schuster, 2024)
In 1987, the only Black person in all Swift River after her Pop disappeared seven years ago, Diamond Newberry, receiving a letter from a relative she's never met, is introduced to two generations of African American Newberry women, gaining a sense of her place in the world and in her family.